Sentiment analysis and knowledge discovery in contemporary business - Rajput, Dharmendra Singh 1985-; Thakur, Ramjeevan Singh 1974-; Basha, Syed Muzamil 1986- (IGI Global, 2019)
"This book explores what drives profitability and more successful customer relationship management. It looks the behavior of any classifier used to classify sentiments in product reviews. It also develops common expert system to classify and visualize the predicted result"--